বাংলাদেশের গ্রাম : অতীত ও ভবিষ্যৎ - ইসলাম, নজরুল, ১৯৫৭- (ঢাকা : প্রথমা প্রকাশন, 2011)
Articles on the socio-economic condition of villages of Bangladesh; includes some articles on the social condition and structure of Indian villages.
গ্রন্থপঞ্জিগত নির্দেশিকা ও নির্ঘণ্ট অন্তর্ভুক্ত।
Donated By Akbar Ali Khan
In Bengali; includes passages in English.
Keywords: Bangladesh -- Rural conditions; India -- Rural conditions